2021
DOI: 10.3390/s22010152
|View full text |Cite
|
Sign up to set email alerts
|

A Way of Bionic Control Based on EI, EMG, and FMG Signals

Abstract: Creating highly functional prosthetic, orthotic, and rehabilitation devices is a socially relevant scientific and engineering task. Currently, certain constraints hamper the development of such devices. The primary constraint is the lack of an intuitive and reliable control interface working between the organism and the actuator. The critical point in developing these devices and systems is determining the type and parameters of movements based on control signals recorded on an extremity. In the study, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Two of the most widely used polymeric carriers of nucleic acids are polyethyleneimine (PEI) and poly (lactic-co-glycolic acid) (PLGA) [215]. PEI has been widely used as the foundation for gene delivery since 1995 as a result of its high transfection effectiveness [236][237][238]. Because nucleic acids are negatively charged, the polymer's positive charge is appropriate for condensing with them to create polyplexes and in general, the PEI is recognized for its remarkable ability to bind to miRs and transfect cells [239,240].…”
Section: Polymer-based Vectorsmentioning
confidence: 99%
“…Two of the most widely used polymeric carriers of nucleic acids are polyethyleneimine (PEI) and poly (lactic-co-glycolic acid) (PLGA) [215]. PEI has been widely used as the foundation for gene delivery since 1995 as a result of its high transfection effectiveness [236][237][238]. Because nucleic acids are negatively charged, the polymer's positive charge is appropriate for condensing with them to create polyplexes and in general, the PEI is recognized for its remarkable ability to bind to miRs and transfect cells [239,240].…”
Section: Polymer-based Vectorsmentioning
confidence: 99%
“… Application of FMG, EMG and EIT. From the top center picture, in a clockwise order: bionic control based on EIT, EMG and FMG [ 109 ]. An EMG gesture recognition system [ 110 ].…”
Section: Figurementioning
confidence: 99%
“…In this section, we will introduce some applications of three techniques in HMI, medical, and healthcare. [109]. An EMG gesture recognition system [110].…”
Section: Applicationmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of simultaneous EIM and EMG can be helpful for a better understanding of EIM, since the muscle contraction component within the EIM signal can be detected and separated using EMG data. Recent studies have shown that the combination of EMG and bioimpedance may detect the muscle contraction more reliably [27][28][29] and may have a high potential for the detection and estimation of the muscle force/torque [30]. A wearable design that makes the device portable for physical activities such as walking, running, sit-to-stand, stairs climbing, etc.…”
Section: Introductionmentioning
confidence: 99%